Altered methylation pattern of the SRD5A2 gene in the cerebrospinal fluid of post-finasteride patients: a pilot study. Issue 8 (August 2019) - Melcangi, Roberto Cosimo; Casarini, Livio; Marino, Marco; Santi, Daniele; Sperduti, Samantha; Giatti, Silvia; Diviccaro, Silvia; Grimoldi, Maria; Caruso, Donatella; Cavaletti, Guido; Simoni, Manuela
Abstract : Context: Post-finasteride syndrome (PFS) occurs in patients with androgenic alopecia after suspension of the finasteride treatment, leading to a large variety of persistent side effects. Despite the severity of the clinical picture, the mechanism underlying the PFS symptoms onset and persistence is still unclear. Objective: To study whether epigenetic modifications occur in PFS patients. Methods: Retrospective analysis of a multicentric, prospective, longitudinal, case–control clinical trial, enrolling 16 PFS patients, compared to 20 age-matched healthy men. Main outcomes were methylation pattern of SRD5A1 and SRD5A2 promoters and concentration of 11 neuroactive steroids, measured by liquid chromatography-tandem mass spectrometry, in blood and cerebrospinal fluid (CSF) samples. Results: SRD5A1 and SRD5A2 methylation analysis was performed in all blood samples ( n  = 16 PFS patients and n  = 20 controls), in 16 CSF samples from PFS patients and in 13 CSF samples from controls. The SRD5A2 promoter was more frequently methylated in CSF of PFS patients compared to controls (56.3 vs 7.7%). No promoter methylation was detected in blood samples in both groups. No methylation occurred in the SRD5A1 promoter of both groups. Unmethylated controls compared to unmethylated SRD5A2 patients showed higher pregnenolone, dihydrotestosterone and dihydroprogesterone, together with lower testosterone CSF levels. Andrological and neurological assessments did not differ between methylated and unmethylated subjects. Conclusions: For the first time, we demonstrate a tissue-specific methylation pattern of SRD5A2 promoter in PFS patients. Although we cannot conclude whether this pattern is prenatally established or induced by finasteride treatment, it could represent an important mechanism of neuroactive steroid levels and behavioural disturbances previously described in PFS.